A review on thin films on indium tin oxide coated glass substrate - Ho, Soon Min (Asian Publication Corporation, 2016)
Preparation and characterization of thin films on indium tin oxide were carried out by many researchers using chemical bath deposition and electro deposition technique. Thin films formation was confirmed by X-ray diffractometer. Meanwhile, compositional, morphological and optical properties of films were studied by means of energy dispersive X-ray, scanning electron microcopy, atomic force microscopy and UV-visible spectrophotometer, respectively.